Food Insecurity and Associated Challenges to Healthy Eating Among American Indians and Alaska Natives With Type 2 Diabetes: Multiple Stakeholder Perspectives. (August 2021) - Stotz, Sarah; Brega, Angela G.; Henderson, J. Neil; Lockhart, Steven; Moore, Kelly; ,
Objective: To examine stakeholder perspectives on food insecurity and associated challenges to healthy eating among American Indian and Alaska Native (AI/AN) adults with type 2 diabetes (T2D).Methods: Focus groups and interviews were conducted with purposively selected stakeholders: AI/ANs with T2D, their family members, healthcare administrators, nutrition and diabetes educators, and national content experts on AI/AN health. Two coders analyzed transcripts using the constant-comparison method.Results: Key themes included (1) rural- and urban-dwelling AI/ANs experience different primary food security and associated challenges; (2) factors contributing to food insecurity extend beyond cost of healthy food; and (3) barriers to consuming fresh, healthy food include cost, preparation time, limited cooking knowledge, and challenges with gardening.Discussion: Resources for AI/ANs with T2D who experience food insecurity and associated challenges to healthy eating should be tailored based on urban versus rural location and should address cost and other barriers to consumption of fresh fruits and vegetables.